UPAYA MENINGKATKAN KOMPETENSI MENGELOLA PEMBELAJARAN PAIKEM MELALUI PENERAPAN SUPERVISI AKADEMIK INDIVIDUAL DENGAN PENDEKATAN NON DIRECTIF - Usman Usman (Tarbawi : Jurnal Pendidikan Islam, 2016)
The purpose of this study is to determine whether through the application of individual academic supervision with a non-directive approach can improve the competence of learning management PAIKEM for teachers SD Negeri 3 Kandangrejo UPTD Education District Klambu Grobogan District. This research was conducted on the subject of all the teachers of the State Elementary School 3 Kandangrejo UPTD Education District Klambu Grobogan District Year lesson 2016/2017. The method used in this research is the school action research. Action Risearch consists of two cycles, one cycle of an individual supervision with non-directive approach while two cycles of individual supervision with non-directive approach. Data collection techniques used are non-test techniques. The instrument used is an observation and assessment sheet. Validation of data using triangulation of sources involving teachers of SD Negeri 3 Kandangrejo. Data analysis used is descriptive analysis followed by reflection. The results of this school research is through the application of individual academic supervision with a non-directive approach can improve the competence of managing PBM PAIKEM of 17.9% from the average of 64 to 78, resulting in the increase of category C into B in the management of PBM PAIKEM for teachers SD Negeri 3 Kandangrejo UPTD Education District Klambu Grobogan District. Keywords: Individual Academic Supervision, PAIKEM, Non Directif Approach.Tujuan penelitian ini adalah untuk mengetahui apakah melalui penerapan supervisi akademik individu dengan pendekatan non direktif dapat meningkatkan kompetensi pengelolaan pembelajaran PAIKEM bagi guru SD Negeri 3 Kandangrejo UPTD Pendidikan Kecamatan Klambu Kabupaten Grobogan. Penelitian ini dilakukan pada subjek penelitian semua guru SD Negeri Negeri 3 Kandangrejo UPTD Pendidikan Kecamatan Klambu Kabupaten Grobogan Tahun pelajaran 2016/2017. Metode yang digunakan dalam penelitian ini adalah penelitian tindakan sekolah. Action Risearch ini terdiri dari dua siklus, siklus satu merupakan supervisi individual dengan pendekatan non direktif sedangkan siklus dua supervisi  individu dengan pendekatan non direktif.  Teknik pengumpulan data yang digunakan adalah teknik non tes. Instrument yang digunakan adalah lembar pengamatan dan penilaian. Validasi data menggunakan trianggulasi sumber yang melibatkan guru SD Negeri 3 Kandangrejo. Analisis data yang digunakan adalah deskriptif analisis yang dilanjutkan refleksi. Hasil penelitian ini adalah melalui penerapan supervisi akademik individual dengan pendekatan non direktif dapat meningkatkan kompetensi mengelola PBM PAIKEM sebesar 17,9 % dari rerata 64 menjadi 78, sehingga terjadi peningkatan kategori C menjadi B dalam pengelolaan PBM PAIKEM bagi guru SD Negeri 3 Kandangrejo UPTD Pendidikan Kecamatan Klambu Kabupaten Grobogan. Kata Kunci : Supervisi, Paikem, Pendekatan non directif.